Answer:
Choice d is correct answer.
Explanation:
Given equation is:
2x² + 3x - 7 = x² + 5x + 39
Move all the terms of all equation using subtraction,we get
2x² + 3x - 7 - x² - 5x - 39 = 0
x² - 2x - 46 = 0 is quardatic equation.
ax²+bx+c = 0 is general quadratic equation.
x = ( -b±√b²-4ac) / 2a is qudratic formula.
comparing quadratic equation with general quadratic equation, we get
a = 1 , b = -2 and c = -46
putting above values in quadratic formula, we get
x = ( - (-2)±√(-2)²-4(1)(-46) ) / 2(1)
x = ( 2 ±√4+184) / 2
x = (2±√188) / 2
x = ( 2±√4×47) / 2
x = (2±2√47 ) / 2
x = 2( 1±√47) /2
x = 1±√47 is the solution of given equation.